The priority of democracy : political consequences of pragmatism - Knight, Jack, 1952- (A Princeton University Press e-book, 2011)
Pragmatism and its consequences are central issues in American politics today, yet scholars rarely examine in detail the relationship between pragmatism and politics. In The Priority of Democracy, Jack Knight and James Johnson systematically explore the subject and make a strong case for adopting a pragmatist approach to democratic politics--and for giving priority to democracy in the process of selecting and reforming political institutions. What is the primary value of democracy? When should we make decisions democratically and when should we rely on markets?